2013
DOI: 10.5897/ajcpath13.004
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological pattern of renal tumours seen in Usmanu Danfodiyo University Teaching Hospital Sokoto, Nigeria

Abstract: Aim: Malignant renal tumour is a relatively rare type of cancer that occurs third in urological tumours after prostate and bladder cancers. Little is known in the literatures about its existence in Sokoto which prompted this research. This study was carried out to determine the prevalence and histopathological pattern of malignant renal tumours in Sokoto, Nigeria. Methods: A total of 11,554 H&E stained sections were reviewed from 2001 to 2012. Patient's data such as age and sex were analyzed from 36 samples wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
13
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 10 publications
7
13
1
Order By: Relevance
“…Excluding the outlier patient aged 8 years, the mean age from this study is 40 ± 13 years. This is within range of the national average of 45± 4 years (peak age in fifth decade) (2,(4)(5)(6)(7)(12)(13)(14)(15)(16)(17)(18)(19). This is about two decades earlier than the pattern described for western countries where the peak age incidence is in the seventh decade (11,20,21).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Excluding the outlier patient aged 8 years, the mean age from this study is 40 ± 13 years. This is within range of the national average of 45± 4 years (peak age in fifth decade) (2,(4)(5)(6)(7)(12)(13)(14)(15)(16)(17)(18)(19). This is about two decades earlier than the pattern described for western countries where the peak age incidence is in the seventh decade (11,20,21).…”
Section: Discussionsupporting
confidence: 64%
“…Frank et al (29) in their study have also observed that only 1% of all tumors less than 1 cm and 9.2% of all tumors less than 2 cm are usually high grade malignancies. The occurrence of CC carcinoma in patients in our setting (47.8%), even though the most common subtype, is lower than the range of between 60%-85.7% (12)(13)(14)(15)(16)(17)(18) documented in other centers in the country and worldwide (30)(31)(32). In contrast, even though there was a high frequency of PC (30.4%), it was within the range of between 23.8% and 46.2% locally reported by others (5,12,17).…”
Section: Discussioncontrasting
confidence: 56%
“…15 The most common histopathological type of renal tumour in the present study was clear cell carcinoma, comprising 31 cases (60.7%). Isah et al 16 (61.5%) and Sascha et al 17 (77.9%) also showed the predominant cell type to be clear cell carcinoma. The second commonest one was papillary carcinoma followed by chromophobe carcinoma, just as the pattern in previous studies.…”
Section: Histopathological Analysismentioning
confidence: 93%
“…These findings also tally with the ones in the literature. 16,17 Microvascular Invasion Microvascular invasion is an important prognosticator in high risk cases for the development of metastatic disease when demonstrated. Capsular invasion may serve as an additional factor in high-risk stratification of patients with localised RCC.…”
Section: Histopathological Analysismentioning
confidence: 99%
“…NBT is the most common malignant tumor of the kidney in children, and it is the commonest childhood tumor [9] in some centers in Africa. Histologically, renal cell carcinoma occurs in three most common forms, namely: clear cell carcinomas, papillary renal cell carcinomas, and chromophobe renal cell carcinomas [12]. From the ongoing, however, the present study aims to determine the occurrence and histopathology patterns of malignant renal tumors including the histologic subtypes in a single multi-national study center, in Benin City, Nigeria.…”
Section: Introductionmentioning
confidence: 99%